Tannin supplementation modulates the composition and function of ruminal microbiome in lambs infected with gastrointestinal nematodes. Issue 3 (13th February 2020) - Corrêa, Patricia Spoto; Mendes, Lucas William; Lemos, Leandro Nascimento; Crouzoulon, Pierre; Niderkorn, Vincent; Hoste, Hervé; Costa-Júnior, Livio Martins; Tsai, Siu Mui; Faciola, Antonio P; Abdalla, Adibe Luiz; Louvandini, Helder
ABSTRACT: This study was carried out to evaluate the effects of tannin supplementation on ruminal microbiota of sixteen lambs infected and non-infected with Haemonchus contortus and Trichostrongylus colubriformis . Animals were fed with hay, concentrate and supplemented with Acacia mearnsii ( A. mearnsii ). The animals were divided into four treatments: two control groups without infection, either receiving A. mearnsii (C+) or not (C-), and two infected groups, one with A. mearnsii (I+) and another without A. mearnsii (I-). Ruminal short-chain fatty acids (SCFA) and metagenome sequencing of ruminal microbiota were used to evaluate the effect of tannin and infection on ruminal microbiome. For SCFA, differences were observed only with A. mearnsii . Total SCFA and acetate molar percentage were decreased in C+ and I+ ( P <0.05). Butyrate, valerate and isovalerate were higher in lambs that received A. mearnsii in the diet ( P <0.05). The infection changed the microbiome structure and decreased the abundance of butyrate-producing microorganisms. In addition, A. mearnsii supplementation also affected the structure the microbial community, increasing the diversity and abundance of the butyrate-producing and probiotics bacteria, amino acid metabolic pathways, purine, pyrimidine and sphingolipid metabolism. Together, our findings indicate that A. mearnsii supplementation modulates important groups related to nitrogen, amino acid, purine and pyrimidine metabolism, in rumen microbiome, affected by gastrointestinal nematodes infection in lambs. Abstract : The metagenome and ruminal parameters was used to understand the effect of tannin supplementation on rumen microbiota of lambs infected with Haemonchus contortus and Trichostrongylus colubriformis.